Dirty laundry : a novel - Bose, Disha (Ballantine Books, 2023)
"A twisty, domestic suspense debut about a clique of mothers that shatters when one of their own is murdered, bringing chaos to their curated idyll. She was the perfect wife, with the perfect life. You would kill to have it... Ciara Murphy has it all - a loving husband, well-behaved children, and a beautiful home. Her circle of friends in their small Irish village go to her for tips about mothering, style, and influencer success - a picture perfect life is easy money on Instagram. But behind the filters, reality is less polished. Enter Mishti Gupta: Ciara's best friend. Ciara welcomed Mishti into her inner circle for being... unlike the other mothers in the group. But discontent in a marriage arranged for her through her parents back in Calcutta, Mishti now raises her young daughter in a country that is too cold among the children of her new friends who look nothing like her. Mishti just wants what Ciara has - the ease with which she moves through the world - and in that sense, she might be exactly like the other mothers. And there's earth mother Lauren Doyle, born, bred, and the butt of jokes in their village. With her disheveled partner and children who run naked in the yard, they're now mostly a happy lot, and unsurprisingly ostracized for being the singular dysfunction to Ciara's immaculate world. When Lauren finds an unlikely ally in Mishti, she decides that her days of ridicule are over. Then Ciara is found murdered, a bloody, mangled thing against the pristine backdrop of her own home, and the house of cards she'd worked so hard to build comes crumbling down. Everyone looks like they have something to gain from Ciara's death, but if you don't want the blame, it's the perfect time to air your enemies' dirty laundry. In this dazzling debut novel, Bose revolutionizes age-old ideas of love and deceit. What ensues is the delicious unspooling of a group of women desperate to preserve themselves"--